Pressure difference between radial and femoral artery pressure in minimally invasive cardiac surgery using retrograde perfusion. Issue 10 (October 2018) - Nakamura, Yoshitsugu; Emmanuel, Sam; Shikata, Fumiaki; Shirai, Chihiro; Ito, Yujiro; Kuroda, Miho
Objective: To investigate whether radial artery pressure is a reliable surrogate measure of central arterial pressure as approximated by femoral artery pressure in minimally invasive cardiac surgery with retrograde perfusion via femoral cannulation. Method: Fifty-two consecutive patients undergoing minimally invasive cardiac surgery were prospectively included in this study. Cardiopulmonary bypass was established via a femoral artery cannulation and femoral vein. Radial and femoral arterial pressures were recorded continuously, and the pressure differential between them was calculated for both systolic and mean arterial pressures. The agreement between measurements from the two arteries was compared using Bland–Altman plots. An interval of 95% limits of agreement of less than 20 mm Hg was set as satisfactory agreement. Results: Average age was 65 ± 14 years. With respect to systolic arterial pressure, 28 patients (54%) had a peak pressure differential between radial and femoral arteries ⩾20 mm Hg. With respect to mean arterial pressure, only five patients (9%) had a peak pressure differential ⩾20 mm Hg. The pressure differential changed with time. Pressure differential in systolic arterial pressure was 5 ± 8 mm Hg until aortic declamping, then increased to a peak of 23 ± 16 mm Hg when cardiopulmonary bypass was turned off. The femoral systolic arterial pressures were significantly greater than radial systolic arterial pressures from time of aortic declamping to 20 min after cardiopulmonary bypass. The Bland–Altman plots revealed large biases and poor agreement in this period. Conclusion: Radial and femoral systolic artery pressure readings can differ significantly in minimally invasive cardiac surgery with retrograde perfusion. Intraoperative arterial pressure management based solely on radial systolic arterial pressure readings should be avoided.